Laser printable polymer compositions
By using a combination of high molecular weight polymer UV light stabilizer and low carbon black concentration, the mechanical properties maintenance problem of the polymer composition under laser printing and UV light exposure is solved, achieving efficient laser printing and long-term stability.
Patent Information
- Application Number
- CN202180060312.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-30
- Filing Date
- 2021-07-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-07-26
AI Technical Summary
The prior art is difficult to achieve laser printing using less than 0.25% by weight of carbon black while maintaining the mechanical properties of the polymer composition, and there are migration and isolation problems with the use of oligomer-hindered amine UV light stabilizers.
A polymer ultraviolet stabilizer with a weight average molecular weight of 5,000 g/mol to 20,000 g/mol and a carbon black of 0.05 wt% to 0.25 wt% is used in the polymer composition to form a laser-printable polymer composition .
It is achieved that the polymer composition maintains 50% or more of the elongation of break after accelerated UV light exposure for 2000 hours while laser printing is enabled using carbon black of lower loads.
Smart Images

Figure BDA0004113752030000121 
Figure BDA0004113752030000131 
Figure BDA0004113752030000132
Abstract
Description
Background Art Technical Field
[0001] The present disclosure relates to compositions, and more particularly to laser printable polymer compositions. Background Art
[0003] Laser beam printing is a method for marking polymer compositions. Laser beam printing is useful because no physical contact between printing ink or polymer composition and printer is required. Further, the process of laser beam printing is fast and simple and can provide markings of good durability.
[0004] Not every polymer composition can be laser printed. For example, polymer compositions often require specific additives and compositions in order to make them laser printable. The requirement to make a polymer composition laser printable may conflict with the design of the polymer composition based on its end use. For example, conventional wire and cable jacketing may contain carbon black at a concentration of about 2 wt % to 3 wt % to ensure 50% retention of elongation at break after 2000 hours of accelerated UV exposure. Unfortunately, conventional carbon black concentrations of about 2 wt % to 3 wt % result in insufficient contrast (i.e., 25% contrast or less) when laser printed.
[0005] Others have attempted to address the above problems by replacing carbon black with ultraviolet ("UV") light stabilizers. For example, European Patent Office Patent Publication No. EP0710570A1 ("the '570 Publication") discloses a group of UV light stabilizers that allow for low carbon black concentrations and provide a laser printable jacket. The UV light stabilizers disclosed in the '570 Publication are (a) a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, (b) 2-(2'-hydroxy-5'-tert-butylphenyl)-3-chlorobenzotriazole, (c) 2-hydroxy-4-m-octyloxybenzophenone, (d) N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and 2, The UV light stabilizers disclosed in the '770 publication are small molecules or oligomeric in nature. For example, UV light stabilizers (b), (c), (e), (f), and (g) are small molecules, while (a) has a number average molecular weight (Mn) of 3100 to 4000, and (d) has an Mn of 2000 to 3100, such that (a) and (d) are oligomeric. As shown in Table 5 of the '570 publication, Example 17A using oligomeric UV light stabilizer (a) is able to produce a polymer composition that can withstand accelerated UV light exposure at less than 2 wt % but greater than 0.3 wt % carbon black. However, Table 3 of the '570 publication shows that oligomeric UV light stabilizer (a) fails to achieve gray contrast greater than 25% at carbon black levels of 0.3 wt % or greater. These results indicate that the use of polymeric UV light stabilizers containing hindered amine moieties requires a compromise between a composition that withstands accelerated UV light exposure and a composition that is laser printable.
[0006] World Intellectual Property Organization Publication No. WO2019068815A1 ("the '815 publication") provides another attempt in the art to solve the problems associated with laser printing wire and cable jacketing, and the attempt uses a synergistic blend of carbon black and an oligomeric hindered amine UV light stabilizer. The '815 publication discloses the use of a synergistic mixture of UV light stabilizers (a) and (d) of the '570 publication in a polymer composition, but requires a carbon black concentration of at least 0.25 wt% to maintain the mechanical properties of the polymer composition after accelerated UV exposure.
[0007] In view of the fact that the combined art cannot obtain polymer compositions using less than 0.25 wt % carbon black by adding oligomeric hindered amine light stabilizers, it is surprising to have discovered a polymer composition comprising 0.05 wt % to 0.25 wt % carbon black and a polymeric UV light stabilizer having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol as measured according to gel permeation chromatography, which polymer composition is laser printable (i.e., greater than 25% gray contrast) and retains 50% or more of its elongation at break after 2000 hours of accelerated UV exposure. Summary of the invention
[0008] The inventors of the present application have surprisingly found that the use of a polymeric UV light stabilizer comprising a hindered amine moiety and having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol as measured according to gel permeation chromatography enables the formation of a polymer composition having 0.05 wt % to 0.25 wt % carbon black, which is laser printable (i.e., gray contrast greater than 25%) and retains 50% or more of its elongation at break after 2000 hours of accelerated UV light exposure. Without being bound by theory, it is believed that the higher molecular weight polymeric UV light stabilizer resists migration and segregation during manufacture and use of the polymer composition compared to the prior art oligomeric UV light stabilizers. The reduced migration of the polymeric UV light stabilizer provides enhanced retention for the stabilizer during extended exposure to UV light. Due to the enhanced retention and maintained dispersion of the stabilizer, the polymer composition is able to retain 50% or more of its elongation at break after 2000 hours of accelerated UV light exposure. The successful use of polymeric UV light stabilizers is surprising considering that an equal weight percentage of oligomeric stabilizers would be successful, but is not as demonstrated in the prior art. Lower loadings of carbon black can be used while the UV light stabilizer remains dispersed and allows the polymer composition to maintain its elongation at break, which makes the polymer composition laser printable.
[0009] The polymer composition is particularly useful as jacketing for wires and cables.
[0010] According to a first feature of the present disclosure, a polymer composition comprises: an ethylene polymer; 0.05 wt% to 0.25 wt% of carbon black, based on the total weight of the polymer composition; and a polymeric ultraviolet light stabilizer comprising a hindered amine portion and having a weight average molecular weight of 5,000 to 20,000 g / mol as measured according to gel permeation chromatography.
[0011] According to a second feature of the present disclosure, the polymer composition includes 95 wt% or more of the ethylene polymer based on the total weight of the polymer composition.
[0012] According to a third feature of the present disclosure, the ethylene polymer has a density of 0.919 to 0.950 g / cc as measured by ASTM D792.
[0013] According to a fourth feature of the present disclosure, the polymer composition further includes an oligomeric ultraviolet light stabilizer having a weight average molecular weight of about 1,000 to about 5,000 g / mol as measured according to gel permeation chromatography.
[0014] According to a fifth feature of the present disclosure, the polymer composition includes 0.25 wt % to 1.0 wt % of the oligomeric ultraviolet light stabilizer, based on the total weight of the polymer composition.
[0015] According to the sixth feature of the present disclosure, the Chemical Abstracts Service registration number of the oligomer UV stabilizer is 136504-96-6 or 71878-19-8.
[0016] According to a seventh feature of the present disclosure, the polymer composition includes 0.10 wt % to 0.25 wt % of carbon black based on the total weight of the polymer composition.
[0017] According to an eighth feature of the present disclosure, the polymer composition includes 0.25 wt % to 2 wt % of the polymer ultraviolet light stabilizer, based on the total weight of the polymer composition.
[0018] According to a ninth feature of the present disclosure, the polymer UV stabilizer has a weight average molecular weight of 8,000 to 12,000 g / mol as measured according to gel permeation chromatography, and further wherein the Chemical Abstracts Service registration number of the polymer UV stabilizer is 136504-96-6.
[0019] According to a tenth feature of the present disclosure, a coated conductor includes a conductor and a polymer composition at least partially disposed around the conductor. DETAILED DESCRIPTION
[0020] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as comprising components A, B, and / or C, the composition may contain A alone; B alone; C alone; A and B in combination; A and C in combination; B and C in combination; or A, B, and C in combination.
[0021] Unless otherwise stated, all ranges are inclusive.
[0022] Test methods refer to the most recent test methods as of the priority date of this document, unless the date is expressed as a two-digit number with a hyphen in the test method number. Reference to a test method includes reference to both the testing association and the test method number. Test method organizations are referenced by one of the following abbreviations: ASTM refers to ASTM International (formerly the American Society for Testing and Materials); EN refers to European Standards; DIN refers to the German Institute for Standardization; and ISO refers to the International Organization for Standardization. When used herein, a Chemical Abstracts Service registry number refers to the most recent chemical or chemical composition assigned to that registry number as of the priority date of this document.
[0023] As used herein, unless otherwise indicated, the term weight percent ("wt %") refers to the weight percent of a component based on the total weight of a polymer composition. The term mole percent ("mol %") refers to the mole percent of a component based on the total moles of the article in which the component is present.
[0024] Unless otherwise provided herein, density is measured according to ASTM D792, Method B. Results are reported in grams (g) per cubic centimeter (g / cc).
[0025] Unless otherwise provided herein, melt index (MI) is measured according to ASTM D1238, Condition 190°C / 2.16 kilogram (kg) weight, and is reported in grams eluted per 10 minutes (g / 10 min).
[0026] "Polymer" means a polymeric compound prepared by polymerizing monomers, whether of the same or a different type.Thus, the generic term polymer encompasses the terms homopolymer, interpolymer, and copolymer.
[0027] Polymer composition
[0028] The present disclosure provides a polymer composition. The polymer composition comprises an ethylene polymer, carbon black and a polymer UV stabilizer ("polymer stabilizer"). The polymer composition may also comprise an oligomer UV stabilizer ("oligomer stabilizer"). As will be explained in more detail below, the polymer composition may be used to form a sheath for coating a conductor.
[0029] Ethylene polymer
[0030] The polymer composition comprises an ethylene polymer. The ethylene polymer may comprise 50 mol % or greater, 60 mol % or greater, 70 mol % or greater, 80 mol % or greater, 85 mol % or greater, 90 mol % or greater, or 91 mol % or greater, or 92 mol % or greater, or 93 mol % or greater, or 94 mol % or greater, or 95 mol % or greater, or 96 mol % or greater, or 97 mol % as measured using nuclear magnetic resonance (NMR) or Fourier transform infrared (FTIR) spectroscopy. % or more, or 97.5 mol % or more, or 98 mol % or more, or 99 mol % or more, while at the same time 100 mol % or less, 99.5 mol % or less, or 99 mol % or less, or 98 mol % or less, or 97 mol % or less, or 96 mol % or less, or 95 mol % or less, or 94 mol % or less, or 93 mol % or less, or 92 mol % or less, or 91 mol % or less, or 90 mol % or less, or
[0031] 85 mol% or less, or 80 mol% or less, or 70 mol% or less, or 60 mol% or less ethylene. Other units of the ethylene polymer may include C3 to C4 α-olefins, or C6 α-olefins, or C8 α-olefins, or C 10 α-olefins, or C 12 α-olefins, or C 16 α-olefins, or C 18 α-olefins, or C 20 Alpha-olefins, such as propylene, 1-butene, 1-hexene, 4-methyl-1-pentene and 1-octene. Other units of ethylene polymers can be derived from one or more polymerizable monomers, which include but are not limited to polar monomers, such as unsaturated esters. Unsaturated esters can be alkyl acrylates, alkyl methacrylates or vinyl carboxylates. The alkyl group can have 1 to 8 carbon atoms, or 1 to 4 carbon atoms. The carboxylate group can have 2 to 8 carbon atoms, or 2 to 5 carbon atoms. Examples of acrylates and methacrylates include but are not limited to ethyl acrylate, methyl acrylate, methyl methacrylate, tert-butyl acrylate, n-butyl acrylate, n-butyl methacrylate and 2-ethylhexyl acrylate. Examples of vinyl carboxylates include but are not limited to vinyl acetate, vinyl propionate and vinyl butyrate. The ethylene polymer can have a polar monomer content of 40 wt% or less, or 35 wt% or less, or 30 wt% or less, or 25 wt% or less, or 20 wt% or less, 15 wt%, or 10 wt%, or 5 wt% or less, or 3 wt% or less, or 1 wt% or less, or 0 wt%, based on the total weight of the ethylene polymer, as measured using nuclear magnetic resonance (NMR) or Fourier transform infrared (FTIR) spectroscopy.
[0032] The density of the ethylene polymer may be 0.900 g / cc or greater, or 0.904 g / cc or greater, or 0.910 g / cc or greater, or 0.915 g / cc or greater, or 0.919 g / cc or greater, or 0.920 g / cc or greater, or 0.921 g / cc or greater, or 0.922 g / cc or greater, or 0.925 g / cc or greater, or 0.926 g / cc or greater, or 0.930 g / cc or greater, or 0.939 g / cc or greater, as measured according to ASTM D792. 5g / cc or more, or 0.940g / cc or more, or 0.945g / cc or more, while 0.950g / cc or less, or 0.940g / cc or less, or 0.935g / cc or less, or 0.930g / cc or less, or 0.925g / cc or less, or 0.920g / cc or less, or 0.919g / cc or less, or 0.915g / cc or less, or 0.910g / cc or less, or 0.905g / cc or less.
[0033] The melt index of the ethylene polymer can be 0.1 g / 10 min or more, or 0.3 g / 10 min or more, or 0.5 g / 10 min or more, or 1.0 g / 10 min or more, or 1.5 g / 10 min or more, or 2.0 g / 10 min or more, or 2.5 g / 10 min or more, or 3.0 g / 10 min or more, or 3.5 g / 10 min or more, or 4.0 g / 10 min or more, or 4.5 g / 10 min or more, or 10.0 g / 10 min or more, or 18 g / 10 min or more, while at the same time, 30.0 g / 10 min or more, or 35.0 g / 10 min or more, or 36.0 g / 10 min or more, or 38.0 g / 10 min or more, or 39.0 g / 10 min or more, or 40.0 g / 10 min or more, or 41.0 g / 10 min or more, or 42.0 g / 10 min or more, or 43.0 g / 10 min or more, or 44.0 g / 10 min or more, or 45.0 g / 10 min or more, or 46.0 g / 10 min or more, or 47.0 g / 10 min or more, or 48.0 g / 10 min or more, or 49.0 g / 10 min or more, or 50.0 g / 10 min or more, or 51.0 g / 10 min or more, or 52.0 g / 10 min or more, or 53.0 g / 10 min or more, or 54.0 g / 10 min or more, or 55.0 g / 10 min or more, or 56.0 g / 10 min or more, or 57.0 g / 10 min or more, or 58.0 g / 10min or less, or 25.0 g / 10min or less, or 20.0 g / 10min or less, or 18.0 g / 10min or less, or 15.0 g / 10min or less, or 10.0 g / 10min or less, or 5.0 g / 10min or less, or 4.5 g / 10min or less, or 4.0 g / 10min or less, or 3.5 g / 10min or less, or 3.0 g / 10min or less, or 2.5 g / 10min or less, or 2.0 g / 10min or less, or 1.5 g / 10min or less, or 1.0 g / 10min or less, or 0.5 g / 10min or less.
[0034] Polymer composition comprises the ethylene polymer of 80wt% to 99wt%.For example, based on the gross weight of polymer composition, polymer composition can comprise 80wt% or more, or 82wt% or more, or 84wt% or more, or 86wt% or more, or 88wt% or more, or 90wt% or more, or 92wt% or more, or 94wt% or more, or 95wt% or more, or 96wt% or more, or 98wt% or more, and 99wt% or less, or 98wt% or less, or 96wt% or less, or 95wt% or less, or 94wt% or less, or 92wt% or less, or 90wt% or less, or 88wt% or less, or 86wt% or less, or 84wt% or less, or 82wt% or less ethylene polymer simultaneously.
[0035] Carbon Black
[0036] The polymer composition includes carbon black. The Chemical Abstracts Service ("CAS") registration number of carbon black is 1333-86-4. Based on the total weight of the polymer composition, the polymer composition can include an amount of 0.05 wt% to 0.25 wt% carbon black. For example, based on the total weight of the polymer composition, the polymer composition can include 0.05 wt% or more, or 0.06 wt% or more, or 0.07 wt% or more, or 0.08 wt% or more, or 0.09 wt% or more, or 0.10 wt% or more, or 0.11 wt% or more, or 0.12 wt% or more, or 0.13 wt% or more, or 0.14 wt% or more, or 0.15 wt% or more, or 0.16 wt% or more, or 0.17 wt% or more, or 0.18 wt% or more, or 0.19 wt% or more, or 0.20 wt% or more, or 0.21 wt% or more, or 0.22 wt% or more, or 0.23 wt% or more, or 0.24 wt% or more, or 0.25 wt% or more. .24wt% or more and at the same time 0.25wt% or less, or 0.24wt% or less, or 0.23wt% or less, or 0.22wt% or less, or 0.21wt% or less, or 0.20wt% or less, or 0.19wt% or less, or 0.18wt% or less, or 0.17wt% or less, or 0.16wt% or less, or 0.15wt% or less, or 0.14wt% or less, or 0.13wt% or less, or 0.12wt% or less, or 0.11wt% or less, or 0.10wt% or less, or 0.09wt% or less, or 0.08wt% or less, or 0.07wt% or less, or 0.06wt% or less of carbon black.
[0037] Carbon black can have an average particle size between about 10 nm to about 300 nm, or 10 nm to 100 nm, or 15 nm to 50 nm as measured using laser diffraction spectroscopy. Carbon black can be added to the polymer composition as a neat or pure component, or can be added as part of a masterbatch combined with one or more other components (e.g., resin, antioxidant and / or processing aid).
[0038] Polymer UV Stabilizer
[0039] The polymer composition comprises a polymer UV stabilizer. The polymer stabilizer comprises one or more hindered amine moieties. As used herein, the hindered amine moiety is present on an aromatic ring so that the lone pair of electrons of the nitrogen atom is conjugated to the amine moiety in the aromatic ring. The Chemical Abstracts Service ("CAS") registration number of an example of a polymer stabilizer comprising a hindered amine moiety is 136504-96-6 and is described as the reaction product of a polymer of N1, N1'-1, 2-ethanediylbis-1, 3-propylenediamine and 2, 4, 6-trichloro-1, 3, 5-triazine and N-butyl-2, 2, 6, 6-tetramethyl-4-piperidinamine. A commercial example of a polymer stabilizer is sold by 3V Sigma USA, Georgetown, South Carolina, USA, under the trade name UVASORB TMHA10 is sold. The weight average molecular weight of the polymer stabilizer, as measured according to gel permeation chromatography, is 5,000 grams per mole (g / mol) to 20,000 g / mol. For example, the weight average molecular weight of the polymer stabilizer, as measured according to gel permeation chromatography, can be 5,000 g / mol or greater, or 6,000 g / mol or greater, or 7,000 g / mol or greater, or 8,000 g / mol or greater, or 9,000 g / mol or greater, or 10,000 g / mol or greater, or 11,000 g / mol or greater, or 12,000 g / mol or greater, or 13,000 g / mol or greater, or 14,000 g / mol or greater, or 15,000 g / mol or greater, or 16,000 g / mol or greater, or 17,000 g / mol or greater, or 18,000 g / mol or greater, or 19,000 g / mol or greater. g / mol or less, or 19,000 g / mol or less, or 18,000 g / mol or less, or 17,000 g / mol or less, or 16,000 g / mol or less, or 15,000 g / mol or less, or 14,000 g / mol or less, or 13,000 g / mol or less, or 12,000 g / mol or less, or 11,000 g / mol or less, or 10,000 g / mol or less, or 9,000 g / mol or less, or 8,000 g / mol or less, or 7,000 g / mol or less, or 6,000 g / mol or less.
[0040] The polymer composition may include a polymer stabilizer in an amount of 0.25 wt % to 2.00 wt % based on the total weight of the polymer composition. For example, the polymer composition may include 0.25 wt % or greater, or 0.50 wt % or greater, or 0.
[0041] 75wt% or more, or 1.00wt% or more, or 1.25wt% or more, or 1.50wt% or more, or 1.75wt% or more, while 2.00wt% or less, or 1.75wt% or less, or 1.50wt% or less, or 1.25wt% or less, or 1.00wt% or less, or 0.75wt% or less, or 0.50wt% or less of a polymer stabilizer.
[0042] Oligomeric UV Stabilizers
[0043] The polymer composition may include an oligomeric UV light stabilizer. The oligomeric stabilizer may include one or more hindered amine moieties. An exemplary oligomeric stabilizer has a CAS registration number of 136504-96-6 and is described as a reaction product of a polymer of N1,N1'-1,2-ethanediylbis-1,3-propylenediamine and 2,4,6-trichloro-1,3,5-triazine and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine. This oligomeric stabilizer is manufactured by 3V Sigma, Inc., Georgetown, South Carolina, USA, under the trade name UVASORB TM Another example of an oligomeric stabilizer has the CAS Registry Number 71878-19-8 and is described as poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]. This oligomeric stabilizer is marketed by BASF, Ludwigshafen, Germany, under the trade name CHIMASSORB TM 944LD for sale.
[0044] The oligomeric stabilizer has a weight average molecular weight of 1,000 to 5,000 g / mol as measured according to gel permeation chromatography. For example, the weight average molecular weight of the polymeric stabilizer can be 1,000 g / mol or more, or 1,500 g / mol or more, or 2,000 g / mol or more, or 2,500 g / mol or more, or 3,000 g / mol or more, or 3,500 g / mol or more, or 4,000 g / mol or more, or 4,500 g / mol or more, while 5,000 g / mol or less, or 4,500 g / mol or less, or 4,000 g / mol or less, or 3,500 g / mol or less, or 3,000 g / mol or less, or 2,500 g / mol or less, or 2,000 g / mol or less, or 1,500 g / mol or less, as measured according to gel permeation chromatography.
[0045] Based on the total weight of the polymer composition, the polymer composition may include an oligomeric stabilizer in an amount of 0.25 wt% to 2.00 wt%. For example, based on the total weight of the polymer composition, the polymer composition may include 0.25 wt% or more, or 0.50 wt% or more, or 0.75 wt% or more, or 1.00 wt% or more, or 1.25 wt% or more, or 1.50 wt% or more, or 1.75 wt% or more, while 2.00 wt% or less, or 1.75 wt% or less, or 1.50 wt% or less, or 1.25 wt% or less, or 1.00 wt% or less, or 0.75 wt% or less, or 0.50 wt% or less of the oligomeric stabilizer.
[0046] additive
[0047] The polymer composition may include one or more additives. Non-limiting examples of suitable additives include antioxidants, colorants, corrosion inhibitors, lubricants, ultraviolet (UV) absorbers or stabilizers, antiblocking agents, flame retardants, coupling agents, compatibilizers, plasticizers, fillers, processing aids and combinations thereof. One or more additives may be combined with the polyethylene resin to form a masterbatch so that a portion or all of the additives may be introduced into the polymer composition in the form of one or more masterbatches.
[0048] The polymer composition may include an antioxidant. Non-limiting examples of suitable antioxidants include phenolic antioxidants, sulfur antioxidants, phosphate antioxidants, and hydrazine metal passivators. Suitable phenolic antioxidants include high molecular weight hindered phenols, methyl substituted phenols, phenols with primary or secondary carbonyl substituents, and multifunctional phenols such as sulfur- and phosphorus-containing phenols. Representative hindered phenols include 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; pentaerythritol tetrakis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate; n-octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; 4,4'-methylenebis(2,6-tert-butyl-phenol); 4,4'-thiobis(6-tert-butyl-o-cresol)2,6-di-tert-butylphenol; 6-(4-hydroxyphenoxy)-2,4-bis(n-octyl-thio)-l,3,5-triazine; 3,5-di-tert-butyl-4-hydroxybenzoic acid (di-n-octylthio)ethyl ester; and hexa[3-(3,5-di-tert-butyl-4-hydroxy-phenyl)-propionic acid]sorbitol ester. The polymer composition may include pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), which may be Irganox TM1010 is commercially available from BASF. A non-limiting example of a suitable methyl-substituted phenol is isobutylene bis (4,6-dimethylphenol). A non-limiting example of a suitable hydrazine-based metal deactivator is oxalyl bis (benzylidene hydrazide). Based on the gross weight of the polymer composition, the polymer composition may include 0wt%, or 0.001wt%, or 0.01wt%, or 0.02wt%, or 0.05wt%, or 0.1wt%, or 0.2wt%, or 0.3wt%, or 0.4wt% to 0.5wt%, or 0.6wt%, or 0.7wt%, or 0.8wt%, or 1.0wt%, or 2.0wt%, or 2.5wt%, or 3.0wt% of an antioxidant.
[0049] The composition may include a processing aid. Non-limiting examples of suitable processing aids include oils, organic acids (such as stearic acid) and metal salts of organic acids (such as zinc stearate). In one embodiment, based on the gross weight of the composition, the composition includes 0wt%, or 0.01wt%, or 0.02wt%, or 0.05wt%, or 0.07wt%, or 0.1wt%, or 0.2wt%, or 0.3wt%, or 0.4wt% to 0.5wt%, or 0.6wt%, or 0.7wt%, or 0.8wt%, or 1.0wt%, or 2.0wt%, or 2.5wt%, or 3.0wt%, or 5.0wt%, or 10.0wt%, or 20.0wt% of a processing aid.
[0050] Based on the total weight of the polymer composition, the composition can include 0 wt% or more, or 0.001 wt% or more, or 0.002 wt% or more, or 0.005 wt% or more, or 0.006 wt% or more, or 0.008 wt% or more, or 0.009 wt% or more, or 0.01 wt% or more, or 0.2 wt% or more, or 0.3 wt% or more, or 0.4 wt% or more, or 0.5 wt% or more, or 1.0 wt% or more, or 2.0 wt% or more, or 3.0 wt% or more, or 4.0 wt% or more, or 5.0 wt% or more, or 10.0 wt% or more, or 15.0 wt% or more, or 20.0 wt% or more, or 30 wt% or more, or 40 wt% or more, or 50 wt% or more of the additive.
[0051] Coated conductor
[0052] The present disclosure also provides a coated conductor. The coated conductor includes a conductor and a coating on the conductor, the coating comprising a polymer composition. The polymer composition is at least partially disposed around the conductor to produce a coated conductor. The conductor may include a conductive metal or an optically transparent structure.
[0053] The method for preparing a coated conductor comprises mixing and heating a polymer composition in an extruder to at least the melting temperature of the polymer components to form a polymer melt blend, and then applying the polymer melt blend to a conductor. The term "onto" includes direct contact or indirect contact between the polymer melt blend and the conductor. The polymer melt blend is in an extrudable state.
[0054] The polymer composition is disposed on and / or around the conductor to form a coating. The coating may be one or more inner layers, such as an insulating layer. The coating may completely or partially cover or otherwise surround or coat the conductor. The coating may be the only component surrounding the conductor. Alternatively, the coating may be a layer of a multi-layer jacket or sheath surrounding the conductor. The coating may directly contact the conductor. The coating may directly contact the insulating layer surrounding the conductor.
[0055] Example
[0056] Test Method
[0057] Elongation at break: According to ASTM D638, using ISO 527 type 5a dog bone, using INSTRU-MET TM Tensile testing to determine elongation at break was performed using a 4201 tensile tester at 5.08 cm / min. The percent retention of elongation was determined by dividing the average elongation at break of the UV aged samples by the elongation at break of the unaged samples. The elongation at break data in Table 3 is reported as the average elongation at break of five samples, with 1 standard deviation also reported.
[0058] Gray contrast: Gray contrast percentage was calculated using ImageJ software (NIH) on markings produced at a beam wavelength of 1064.6 nm, a frequency of 60 kHz, an intensity of 90%, and a marking speed of 2000 mm / sec.
[0059] Molecular weight: Unless otherwise specified herein, molecular weight is weight average molecular weight and is determined by gel permeation chromatography. Gel permeation chromatography (GPC) was performed on a Waters modular chromatography HPLC / SEC system. The mobile phase was tetrahydrofuran with 0.08 mole of diethanolamine and degassed with helium. Two mesoporous columns from Polymer Laboratories were used. GPC was performed at a temperature of 30°C and a flow rate of 0.6 liters per minute. The concentration used was greater than 10 milligrams per milliliter, and the injection volume was 50 microliters. GPC measurements were performed for a period of 40 minutes. GPC calibration was performed based on 8 polystyrene standards with narrow molecular weight distribution (peak molecular weight between 382 g / mol and 95000 g / mol) using a 3rd order polynomial.
[0060] Material
[0061] Materials used in the examples are provided below.
[0062] The resin is UNIPOL having a density of 0.935 g / cc and a melt index (MI, I2) of 0.6 g / 10 min (190°C / 2.16 kg). TM Gas phase unimodal medium density polyethylene.
[0063] CBMB is a carbon black masterbatch containing 45 wt% carbon black and available from The Dow Chemical Company, Midland, MI, USA.
[0064] HALS is CAS Registry No. 70624-18-9 and is available under the trade name CHIMASSORB TM 944 is a hindered amine light stabilizer commercially available from BASF, Ludwigshafen, Germany.
[0065] HA10 is a polymeric UV stabilizer having CAS Registry Number 136504-96-6 and a weight average molecular weight of about 10,000 as measured by gel permeation chromatography. HA10 is available under the trade name UVASORB TM HA10 was commercially available from 3V Sigma USA, Georgetown, South Carolina, USA.
[0066] HA88 is an oligomeric UV stabilizer having a CAS registration number of 136504-96-6 and a weight average molecular weight of about 3,000 as measured by gel permeation chromatography. HA88 is available under the trade name UVASORB TM HA88 was commercially available from 3V Sigma USA, Georgetown, South Carolina, USA.
[0067] AO is poly(1,2-dihydro-2,2,4-trimethylquinoline) with CAS Registry Number 26780-96-1 and is available under the trade name NAUGARD TM Super Q stabilizer is commercially available from Addivant, Danbury, Connecticut, USA.
[0068] PA is available under the trade name DYNAMAR TM FX 5912 is a fluororesin processing aid commercially available from 3M, Saint Paul, Minnesota, USA.
[0069] Resin 2 is UNIPOL having a density of 0.945 g / cc and a melt index (MI, I2) of 0.8 g / 10 min (190°C / 2.16 kg). TM Gas phase unimodal high density polyethylene.
[0070] Sample preparation
[0071] Preheat the BRABENDER to 180°C TM Inventive Examples ("IE"), Comparative Examples ("CE"), and Test Samples (S) were prepared on a mixer and mixed using a roller blade at 40 revolutions per minute ("rpm"). First, all resins were added and allowed to melt. Stabilizers and processing aids were then added and allowed to melt for 5 minutes. The Examples and Test Samples were then cold pressed, coarsely pelletized, and mixed on a BRABENDER. TM The strands were extruded on an extruder with a temperature profile of 150°C to 180°C, 40 rpm, and a 20 / 40 / 20 filter screen set. The strands were then pelletized to form pellets.
[0072] The plates were prepared by compression molding the pellets on an arbor press preheated to 180°C. The pellets were placed in a 1.905 millimeter (mm) mold. The samples were heated to 180°C for 4 minutes and then pressed at a pressure of 3.45 MPa for 3 minutes, followed by 17.24 MPa for 3 minutes. The samples were cooled in the press at 15°C / minute until approximately 23°C was reached and then conditioned according to the test requirements. The dog bone specimens were cut from the compression molded plates.
[0073] The dog bone samples were UV aged according to Telecordia GR-20 with multiple cycles: 70°C at 0.7 W / (m 2nm) for 20 hours followed by dark condensation at 55° C. for 4 hours. The samples were pulled at 1000 hour and 2000 hour increments.
[0074] Compression molded plaques (1.27 mm x 101.6 mm x 101.6 mm) of the test samples were prepared and laser marked according to the parameters of Table 1.
[0075] Table 1
[0076]
[0077]
[0078] result
[0079] Table 2 provides the composition and gray contrast of the test samples. The purpose of the test samples was to demonstrate the change in gray contrast with carbon black concentration. The CBMB values of Table 2 provide the weight percent of CBMB based on the total weight of the test sample and the carbon black weight percent in parentheses.
[0080] Table 2
[0081]
[0082] As can be seen from Table 2, both Test Sample 1 and Test Sample 2 have sufficiently low carbon black levels to achieve a gray contrast ratio greater than 25%. Therefore, Test Sample 1 and Test Sample 2 are laser printable. Test Samples S3 to S6 show a gray contrast ratio of 25% or less, which means that compositions with a carbon black weight percentage of 0.38 and greater are not laser printable.
[0083] The compositions of IE1 to IE4 and CE1 to CE3 are provided in Table 3. Table 3 also provides mechanical testing data for the initial state (ie, no accelerated UV aging) and the UV aged state after 1000 hours ("h") or 2000 hours of accelerated UV exposure.
[0084] Table 3
[0085]
[0086] As can be seen from Table 3, IE1 to IE4 all have sufficiently low carbon black concentrations to enable laser printing, and therefore IE1 to IE4 are believed to be laser printable. Further, IE1 to IE4 all retain 50% or more of their elongation at break after 2000 hours of accelerated UV exposure. IE1 demonstrates that the use of a polymer stabilizer without an additional oligomeric stabilizer can allow the formation of a laser printable composition that retains 50% or more of its elongation at break after 2000 hours of accelerated UV exposure. IE2 to IE4 each demonstrate that in addition to the polymer stabilizer, an oligomeric stabilizer of the same or different type as the polymer stabilizer can be used and still achieve a laser printable composition that retains 50% or more of its elongation at break after 2000 hours of accelerated UV exposure. CE1 with 2.55 wt% carbon black retains 50% or more of its elongation at break after 2000 hours of accelerated UV exposure as expected, but is not laser printable based on the understanding provided by Table 2. CE2 and CE3 demonstrate that in the absence of polymer stabilizers, due to low carbon black levels, the compositions can be laser printable but fail to retain 50% or more of their elongation at break after 2000 hours of accelerated UV exposure.
Claims
1. A polymer composition, comprising: Ethylene polymers; 0.05 wt % to 0.25 wt % of carbon black, based on the total weight of the polymer composition; and 0.25 wt % to 2 wt % of a polymeric UV stabilizer, based on the total weight of the polymer composition, the polymeric UV stabilizer comprising a hindered amine moiety and having a weight average molecular weight of 8,000 g / mol to 12,000 g / mol as measured by gel permeation chromatography; wherein the hindered amine moiety is present on an aromatic ring such that the lone pair of electrons of the nitrogen atom is conjugated to the amine moiety in the aromatic ring.
2. The polymer composition according to claim 1, wherein the polymer composition comprises 95 wt% or more of the ethylene polymer based on the total weight of the polymer composition.
3. The polymer composition of any one of claims 1 to 2, wherein the ethylene polymer has a density of 0.919 g / cc to 0.950 g / cc as measured by ASTM D792.
4. The polymer composition according to any one of claims 1 to 2, wherein the polymer composition further comprises: An oligomeric ultraviolet light stabilizer having a weight average molecular weight of about 1,000 g / mol to about 5,000 g / mol as measured by gel permeation chromatography. 5 . The polymer composition of claim 4 , wherein the polymer composition comprises 0.25 wt % to 1.0 wt % of the oligomeric UV stabilizer based on the total weight of the polymer composition.
6. The polymer composition according to claim 4, wherein the oligomeric UV stabilizer has a Chemical Abstracts Service Registry Number of 136504-96-6 or 71878-19-8.
7. The polymer composition according to any one of claims 1 to 2, wherein the polymer composition comprises 0.10 wt% to 0.25 wt% of carbon black, based on the total weight of the polymer composition.
8. The polymer composition according to any one of claims 1 to 2, wherein the polymer composition comprises 0.25 wt% to 0.50 wt% of the polymeric UV stabilizer, based on the total weight of the polymer composition.
9. The polymer composition according to any one of claims 1 to 2, wherein the polymer UV stabilizer has a Chemical Abstracts Service registration number of 136504-96-6.
10. The polymer composition according to any one of claims 1 to 2, wherein the polymer UV stabilizer is the reaction product of a polymer of N1,N1'-1,2-ethanediylbis-1,3-propylenediamine and 2,4,6-trichloro-1,3,5-triazine and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine.
11. A coated conductor, comprising: conductor; as well as The polymer composition of any one of claims 1 to 10, wherein the polymer composition is at least partially disposed around the conductor.
Citation Information
Patent Citations
Polymeric composition and process of laser beam printing the surface of said composition
EP0710570A1
Polyolefin composition for enhanced laser printing
WO2019068815A1
Polyolefin composition for enhanced laser printing
CN111108002A
Synergistic stabilizer mixture
CN1137541A